Penerapan Analisis Titik Impas Sebagai Dasar Perencanaan Laba Di Pt Indofood CBP Sukses Makmur Tbk - Nur Jannah, Fitri Ussaefa; Anindita, Alya; Elza Surachman, Ade (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2025)
The main goal of the company is to achieve sustainable growth and increase profits through effective business strategies, including boosting sales in terms of both volume and revenue, which significantly affect profit achievement. Break-even analysis is essential for estimating the profits from product sales. This study aims to evaluate the application of break-even analysis in profit planning at PT Indofood CBP Sukses Makmur Tbk. The research uses a qualitative method with descriptive data from the company's financial reports, books, and journals as secondary data sources. The sampling technique employed is purposive sampling, with a sample of financial reports from 2019 to 2023. The results indicate that the company’s sales have exceeded the established break-even point. However, to maximize profits, the company needs to implement effective marketing strategies, such as attractive promotional pricing while ensuring that revenues remain above the break-even point. Furthermore, a product bundling strategy can significantly increase sales volume, which is crucial for cost efficiency, competitiveness, and achieving the company’s growth targets.